2001
DOI: 10.1128/jb.183.20.5904-5910.2001
|View full text |Cite
|
Sign up to set email alerts
|

Translocation-Specific Conformation of Adenylate Cyclase Toxin from Bordetella pertussis Inhibits Toxin-Mediated Hemolysis

Abstract: Bordetella pertussis adenylate cyclase (AC) toxin belongs to the RTX family of toxins but is the only member with a known catalytic domain. The principal pathophysiologic function of AC toxin appears to be rapid production of intracellular cyclic AMP (cAMP) by insertion of its catalytic domain into target cells (referred to as intoxication). Relative to other RTX toxins, AC toxin is weakly hemolytic via a process thought to involve oligomerization of toxin molecules. Monoclonal antibody (MAb) 3D1, which binds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 36 publications
6
57
0
Order By: Relevance
“…The overall efficiency of translocation (approximately 80% of total tBLM-bound CyaA) observed in vitro compares favorably with that measured previously on sheep erythrocytes (32,43). Furthermore, no translocation was observed with the nonacylated proCyaA protein or after preincubation of CyaA with mAb 3D1, which had been previously shown to block the entry of CyaA into eukaryotic cells (30,33,38). This finding further supports our contention that our in vitro assay captures the essential features of the authentic physiological processes occurring with living cells.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The overall efficiency of translocation (approximately 80% of total tBLM-bound CyaA) observed in vitro compares favorably with that measured previously on sheep erythrocytes (32,43). Furthermore, no translocation was observed with the nonacylated proCyaA protein or after preincubation of CyaA with mAb 3D1, which had been previously shown to block the entry of CyaA into eukaryotic cells (30,33,38). This finding further supports our contention that our in vitro assay captures the essential features of the authentic physiological processes occurring with living cells.…”
Section: Discussionsupporting
confidence: 68%
“…mAb 3D1 Blocks CyaA Translocation Across the tBLM. Gray et al (33) previously reported that a monoclonal antibody, mAb 3D1, which recognizes an epitope located between residues 373 and 399 of CyaA at the C-terminal end of the catalytic domain, does not affect the adenylate cyclase activity of the toxin or its capacity to bind to target cells, but does inhibit delivery of the catalytic domain into the cytosol of target cells (erythrocytes or J774A.1 cells). Thus, we tested the effect of mAb 3D1 in our in vitro translocation assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6C). In contrast, 3D1, a neutralizing IgG that blocks translocation of the catalytic domain (57), and 2A12, a neutralizing antibody with unclear mode-ofaction, had no effect. Minimal nonspecific binding was observed under these assay conditions.…”
Section: Volume 290 • Number 6 • February 6 2015mentioning
confidence: 76%
“…Escherichia coli XL-1 Blue cells (Stratagene, La Jolla, CA) containing the appropriate plasmid construct (wild-type [WT] ACT or inactive ACT) were used for toxin production as previously described (23,29). Cultured bacteria were centrifuged, and the resulting pellet was resuspended in 50 mM Tris (pH 7.5), sonicated, and extracted with 8 M urea.…”
Section: Methodsmentioning
confidence: 99%